2019
DOI: 10.1186/s13195-019-0535-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between increased levels of amyloid-β oligomers in plasma and episodic memory loss in Alzheimer’s disease

Abstract: ObjectiveThe objectives of this study were to investigate whether the plasma levels of oligomeric amyloid-β (OAβ) were affected in Alzheimer’s disease (AD) and to examine the associations (or possible correlations) between plasma OAβ levels and memory performance.MethodThirty subjects with AD and 28 cognitively normal controls were recruited in the study. The multimer detection system (MDS) was used to measure the levels of OAβ in the plasma. In addition to assessing the general cognitive function with the Min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…While techniques used in some studies, such as immunoprecipitation mass spectrometry [ 28 , 29 ], are labor-intensive and time-consuming, the Simoa assays and the MDS method allow high-throughput analysis. The MDS method highly resembles an ELISA in simplicity and automation possibilities [ 7 , 18 , 39 ] and as such, allows broad implementation. Another added value of our study is that we have tested the plasma MDS-OAβ assay in a heterogeneous cohort including other neurodegenerative or neuropsychiatric disorders besides the clinical AD spectrum, while previous plasma Aβ included primarily cohorts which contained the clinical AD spectrum (i.e., healthy controls, MCI, or AD dementia).…”
Section: Discussionmentioning
confidence: 99%
“…While techniques used in some studies, such as immunoprecipitation mass spectrometry [ 28 , 29 ], are labor-intensive and time-consuming, the Simoa assays and the MDS method allow high-throughput analysis. The MDS method highly resembles an ELISA in simplicity and automation possibilities [ 7 , 18 , 39 ] and as such, allows broad implementation. Another added value of our study is that we have tested the plasma MDS-OAβ assay in a heterogeneous cohort including other neurodegenerative or neuropsychiatric disorders besides the clinical AD spectrum, while previous plasma Aβ included primarily cohorts which contained the clinical AD spectrum (i.e., healthy controls, MCI, or AD dementia).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a multimer detection system employing two antibodies with overlapping N-terminal Aβ-epitopes for measuring Aβ oligomerization after spiking synthetic Aβ into blood plasma samples has been developed [ 27 ]. Correlations between the plasma oligomerized Aβ and CSF Aβ 42 , amyloid-positron-emission tomography (PET) results [ 28 ], and measures of cognitive functions [ 29 , 30 ] were reported. Other research groups discovered that the plasma ratios Aβ 42 /Aβ 40 , Aβ 1–40 /Aβ 1–42 , and APP 669–711 /Aβ 1-42 (i.e., Aβ −3–40 /Aβ 1–42 ), as measured by immunoprecipitation followed by mass spectrometry, predicted brain amyloid pathology with high accuracy [ 19 , 20 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hwang et al [25] confirmed that the CERAD scores decreased as the disease progressed through three years of follow-up of participants in the cognitive normal, SCD, MCI, and ADD groups, and CSF Aβ42 levels in each group also decreased in correlation. In 2019, Meng et al [14] described that an increase in MDS-OAβ levels in AD patients correlated with episodic memory loss. Other studies have reported that scores on language-related evaluative tasks such as word list memory and word list recall reflect AD-associated cognitive and memory function changes [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the plasma AβO level in AD highly correlates with CSF Aβ42 and Pittsburgh compound B (PiB) PET standard uptake ratio [13]. In addition, the elevated plasma OAβ level showed a strong correlation with cognitive performance in patients with AD, including an inverse correlation with scores on the mini-mental status examination (MMSE), cognitive abilities screening instrument, the common objects memory test, and a positive correlation with the Alzheimer's disease assessment scale-cognitive portion scores [14]. The level of these biomarkers has been reported to correlate with cognitive performance, especially in patients within the mild cognitive impairment (MCI)-AD continuum, but this association is still controversial and it is unclear whether this correlation is found even in non-AD dementia.…”
Section: Introductionmentioning
confidence: 98%